Calcium triggers an intramolecular association of the C2 domains in synaptotagmin - García, Ricardo A. (The National Academy of Sciences, 2000)
Synaptotagmin I is a critical component of the synaptic machinery that senses calcium influx and triggers synaptic vesicle fusion and neurotransmitter release. Fluorescence resonance energy transfer studies conducted on synaptotagmin demonstrate that calcium concentrations required for fusion induce a conformational change (EC(50) ≈ 3 mM) that brings the two calcium-binding C2 domains in synaptotagmin closer together. Analytical ultracentrifugation studies reveal that synaptotagmin is monomeric under these conditions, indicating that this calcium-triggered association between the C2 domains is intramolecular, rather than intermolecular. These results suggest a mechanism for synaptotagmin function at the presynaptic plasma membrane that involves the self-association of C2 domains.